Physiopathologie and Electrophysiologic Changes of the Inner Ear in Hearing Losses (Annals of Medical Research, 2021)
None
Keywords: s : Electrophysiology, hearing disorders, sensorineural-conductive-high frequency-noise induced- partial hearing loss, labyrinth